Study on the cultural communication preferences of teachers - Kocabas, Ibrahim (Emerald Group Publishing Ltd, 2009)
Purpose - The purpose of this paper is to look at the communication preferences of teachers on the basis of high- and low-context distinction. Design/methodology/approach - In total, 275 teachers employed in primary schools in Elazig, Malatya, and Diyarbakir provinces were chosen as the sample group. Cultural communication scale-Turkish scale developed by Erdem was applied to measure communication tendencies of teachers. Findings - At the end of the paper, during which high- and low-context dimensions are treated separately, high-context communication tendencies of teachers are found to be more dominant than their low-context communication tendencies. Communication tendencies have also been compared in terms of demographic variables and it is evident that variables such as marital status, education level, income level, age, and employment period have resulted in differences in communication tendencies. Originality/value - The paper presents a study on the cultural communication preferences of teachers from a Turkish perspective.
Keywords: Communication; Culture; Teachers; Turkey